What Explains the Rise in Food Price Volatility? - Roache, Shaun (Washington, D.C. : International Monetary Fund, 2010)
The macroeconomic effects of large food price swings can be broad and far-reaching, including the balance of payments of importers and exporters, budgets, inflation, and poverty. For market participants and policymakers, managing low frequency volatility-i.e., the component of volatility that persists for longer than one harvest year-may be more challenging as uncertainty regarding its persistence is likely to be higher. This paper measures the low frequency volatility of food commodity spot prices using the spline- GARCH approach. It finds that low frequency volatility is positively correlated across different commodities, suggesting an important role for common factors. It also identifies a number of determinants of low frequency volatility, two of which-the variation in U.S. inflation and the U.S. dollar exchange rate-explain a relatively large part of the rise in volatility since the mid-1990s.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet